A data analysis model based on control charts to monitor online learning processes. (9th July 2009) - Juan, Angel A.; Daradoumis, Thanasis; Faulin, Javier; Xhafa, Fatos
This paper discusses the convenience of using data analysis techniques to monitor e-learning processes. It also proposes a model to monitor online students' academic activity and performance. Using data from log files and databases, this model determines which information has to be provided to online instructors and students. These reports allow instructors to: classify students according to their activity and learning outcomes, track their evolution, and identify those who might need immediate assistance. They also provide students with a periodical feedback which makes them aware of how they are performing as compared with the rest of the class.